OTAK DAN AKAL DALAM AYAT-AYAT NEUROSAINS - Fu`ad Arif Noor (LP3M Universitas Sains Al Qur'an, 2018)
Neuroscience, are simply the science devoted to learning Neoron(nerve cells). Nerve cells make up the nervous system, both thecentral nervous system (brain and spinal cord) and the peripheralnerves (31 pairs and 12 pairs of spinal nerve head). A nerve cellitself is not the smallest unit away from the nerve cell, the smallestunit of nerve cells (neurons) are the synapses ie the meeting point oftwo nerve cells move and pass the information (neurotransmitters).At the level of molecular biology, the smallest unit is like genes(genetic studies). Generally, the neuroscientist focused on nervecells in the brain. In the Qur'an sense has a glorious position. It wasevident the word